LINGUISTIC AND METHODICAL BASES OF STUDYING TEXT STRUCTURE - Mavlonova Klaraxon Maxmutovna (Journals Park Publishing, 2024)
In the course of research, what requirements are set in the state educational standard and curriculum of the subject of the mother tongue in relation to the structure of the text, what is being studied at school, what materials and opportunities are available in the textbooks, using a questionnaire to study the attitude of teachers to teaching the structure of the text, to study their professional preparation, to pay attention to some serious mistakes made by students in the process of composing a text, to draw methodical conclusions based on them, and on this basis to analyze the State educational standards, curricula and textbooks of the mother tongue subject, as well as the methodical manuals related to them; conducting a survey among native language teachers and analyzing the results; tasks such as identifying some serious mistakes made by students in composing a text were carried out. Mother tongue textbooks can clearly demonstrate the current state of teaching text structure: students can clearly demonstrate the range of information they are getting about the structure of the text, and the skills and abilities they are developing.
Keywords: textbook, text, text structure, text types, theoretical information, exercise, questions and assignments, essay, plan, editing, skill, qualification.